Internationaler Tourismus in Indien - Stang, Friedrich (ERDKUNDE, 1979)
India has not followed other developing countries in pushing ahead with mass tourism centred on beaches but has continued to be a country for the tourist interested in its culture; tourism also does not play a prominent role as a foreign exchange earner. On the other hand, the tourist industry is of special interest to a country like India because it offers employment and opportunities for the development of economically-weak regions. International tourism in India concentrates on a few target areas which can be ordered hierarchically. Centres of the highest order are the international airports with certain national airports as their subcentres. The centres serve only very limited areas of their Umland. This spatial pattern is caused by the lack of infrastructure for touring a country the size of India, but also by the fact that tourists to India have covered long distances to get there and want to visit the greatest possible number of prominent tourist attractions within a short time. For the future an extension of the length of stay should be aimed at by offering the cultural tourist a combination of sightseeing tour and recreational holiday. The development of beaches in the vicinity of existing smaller airports and the promotion of Hill Stations, with their established range of hotels could serve this purpose well. These new sub-centres would not only have the effect of further extending tourism to new parts of India but could also be considered as bases for a step by step expansion of tourist activities into their Umland. In this concept the less sophisticated national tourism and that from neighbouring countries could be of additional help in paving the way for a further spread of tourism in India.